The reciprocal relationship between mathematics self-efficacy and mathematics performance in US high school students: Instrumental Variables estimates and gender differences - Sakellariou, Chris (2022)
Objective: To investigate the reciprocal relationship between high school students’ academic self-efficacy and achievement in mathematics using US data from the HSLS:2009 and first follow-up longitudinal surveys, while accounting for biases in effect estimates due to unobserved heterogeneity.